Preparasi Mikrosfer Fraksi Etil Asetat Herba Sambiloto (Andrographis paniculata Nees) dengan Metode Semprot Kering - IDAH ROSIDAH; WAHONO SUMARYONO; SILVIA SURINI (Fakultas Farmasi Universitas Pancasila, 2012)
Sambiloto (Andrographis paniculata Nees) is a medicinal plant containing andrographolide as its primary bioactive component, which has been shown to inhibit breast cancer cell proliferation. Andrographolide is a diterpene lacton and sparingly soluble in water. The aim of this study is to prepare microspheres of A . paniculata ethylacetate fraction by microencapsulation using spray drying method. The ethyl acetate fraction of A. paniculata herbs was microencapsulated using PVP K30 and HPMC as the coating polymer in different ratios of 1:5; 1:7,5 and 1:10. Microspheres containing the ethyl acetate fraction of A. paniculata herbs were characterized in term of recovery factor, morphology, particle size distribution, water content and entrapment efficiency. The results showed that the A. paniculata microspheres have the recovery factor of 19,50% to 31,64%, spherical shape varies from smooth surface to irregular shape, particles size of 1,44% to 19,23 µm, moisture content of 5,15% to 13,44%, and entrapment echiency between 94,83 to 112,15%.